Improving Community Knowledge on Blood Glucose Control through Health Education in Type 2 Diabetes Mellitus - Sintiya Halisya Pebriani; Lily Marleni; Dessy Suswitha (Jurnal Pengabdian Masyarakat Lentora, 2026)
Type 2 diabetes mellitus is a non-communicable disease with a prevalence that continues to increase worldwide and in Indonesia. In Indonesia, diabetes mellitus has risen from 7th to 5th place globally, with 19.5 million sufferers and is projected to reach 28.6 million people by 2045, while in South Sumatra there were 605,570 cases recorded in 2023. Type 2 DM is at risk of causing complications when blood glucose levels are not controlled, while low public knowledge regarding blood glucose control is one of the contributing factors. This community service activity aimed to improve public knowledge regarding blood glucose level control in patients with type 2 diabetes mellitus.The activity was conducted on July 26, 2025, in RT 25, Pulokerto Village, Gandus District, Palembang, involving 31 participants. Health education was delivered through lectures, discussions, and question-and-answer sessions using leaflet media. Knowledge levels were evaluated using pre-test and post-test questionnaires administered before and after the educational intervention. The evaluation results showed an improvement in participants’ knowledge after receiving education. Before the counseling session, the majority of participants had a moderate level of knowledge (48.4%) and poor knowledge (32.3%), while only 19.4% had good knowledge. After the counseling session, most participants had a good level of knowledge (80.6%), while the remaining 19.4% had a moderate level of knowledge. This community service activity showed that counseling was effective in improving participants’ knowledge. Before the activity, most participants had moderate and poor knowledge, while after the activity, the majority were in the good knowledge category.